Enhancing Students' Critical Thinking Skills: A STEM-Integrated Problem-Based Learning Model - Utami, Vemia; Viyanti, Viyanti; Permadi, Dimas (Jurnal Materi dan Pembelajaran Fisika, 2025)
This research seeks to illustrate the enhancement of students' critical thinking abilities by adopting a problem-based learning model that employs a STEM approach. The study employed an experimental design that included a non-equivalent control group. Information was gathered using test questions about the subject of sound waves. The data on critical thinking skills were evaluated through the N-gain test, normality assessment, homogeneity assessment, paired sample t-test, independent sample t-test, and effect size analysis. The findings showed that the average N-gain of critical thinking abilities in the experimental group was 0.64, whereas in the control group it was 0.29, with both classified as moderate. The paired sample t-test produced a significance value. A (2-tailed) value of 0.000 shows a notable difference in critical thinking abilities before and after the educational process. The findings from the independent sample t-test indicated a significance. (2-tailed) value of 0.000, signifying a difference in the mean N-gain of critical thinking abilities between the experimental and control groups. The effect size analysis indicated a value of 0.82, which was classified as large. According to these findings, the problem-based learning model incorporating a STEM framework can significantly improve students’ critical thinking abilities